The Fidelity of Integrating TPSR and Culturally Relevant Pedagogy through Physical Activity in Educational Contexts - Mines, Erika; Craddock, Christine; Pinkerton, Brittany (Journal of Physical Education and Sport Pedagogy, 2024)
Physical activity has been shown to be beneficial to youth in comprehensive ways including increased time on task, academic performance, social interactions, and emotional awareness. One physical activity model commonly used in physical education and sport is the Teaching Personal and Social Responsibility model (TPSR) which integrates life skills and values into these contexts. This research evaluates fidelity of the TPSR model when extended and administered in a program that focuses on culturally relevant pedagogy and academic content literacies through physical activity. By utilizing the TPSR checklist, participant journal entries, and a participant interview, we found the TPSR model can still be implemented effectively with an academic emphasis. Certain aspects of TPSR were challenged like participant behavior of encouraging others, particularly during low enrollment. While having a larger number of participants can present different challenges, physical activity and academic growth remain key considerations for health of youth. Likewise, physical literacy and content literacy are vital academic aspects of holistic youth development and the findings confirm these areas need not be viewed as exclusive and distinct in educational practice. Those leading in physical literacy contexts and content literacy can use TPSR as a valid framework to successfully engage youth in integrated aspects of each discipline.